External cost analysis of nuclear fuel cycle comparing direct disposal and pyroprocessing in Korea. (December 2022) - Kim, Sungki; Kim, Kwangrag; Kim, Jinseop; Kim, Geonyoung; Cho, Dongkeun; Bang, Sungsig
Abstract: This study presented the external cost estimation results for direct disposal and the pyro-SFR nuclear fuel cycle. Economic evaluations of the nuclear fuel cycle thus far have focused on internal costs, using electricity generation costs. However, after the Fukushima nuclear power plants accident in Japan, public interest in nuclear safety has increased. Therefore, the importance of external costs such as the accident response cost has been highlighted. Environmental groups argue that external social costs should be internalized in nuclear electricity generation costs. Therefore, estimating external costs for the nuclear fuel cycle, which is highly likely to be adopted in the future, is necessary. External costs are social costs and mainly consist of accident response costs, energy supply security costs, and public acceptance costs. In particular, in order to estimate the public acceptance costs in this study, the desired amount of subsidy provided by the government was determined using the survey results of local residents of nuclear power plants and nuclear experts. In the end, electricity generation unit costs including external cost were estimated to be 0.0474 GBP/kWh and 0.0514 GBP/kWh for direct disposal and the pyro-SFR nuclear fuel cycle, respectively. Therefore, in terms of economics, direct disposal would be advantageous over the pyro-SFR nuclear fuel cycle. Highlights: The external cost of direct disposal was estimated to be 0.0076 GBP/kWh. The external cost of pyro-SFR fuel cycle was estimated to be 0.0042 GBP/kWh. The generation costs of direct disposal were estimated to be 0.0474 GBP/kWh. The generation costs of pyro-SFR fuel cycle were estimated to be 0.0514 GBP/kWh. Direct disposal would be advantageous over the pyro-SFR nuclear fuel cycle.